2020
DOI: 10.1038/s41746-020-00357-5
|View full text |Cite
|
Sign up to set email alerts
|

Belief of having had unconfirmed Covid-19 infection reduces willingness to participate in app-based contact tracing

Abstract: Contact tracing and lockdown are health policies being used worldwide to combat the coronavirus (COVID-19). The UK National Health Service (NHS) Track and Trace Service has plans for a nationwide app that notifies the need for self-isolation to those in contact with a person testing positive for COVID-19. To be successful, such an app will require high uptake, the determinants and willingness for which are unclear but essential to understand for effective public health benefit. The objective of this study was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
(15 reference statements)
7
36
1
Order By: Relevance
“…There are also similarities between the two sets of results. Similar to us, [ 25 ] found that advanced age (i.e., 80 and above) was associated with decreased likelihood of participation. In addition, a reduced understanding of government rules and advice on the lockdown at the time was associated with reduced willingness to download the app.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…There are also similarities between the two sets of results. Similar to us, [ 25 ] found that advanced age (i.e., 80 and above) was associated with decreased likelihood of participation. In addition, a reduced understanding of government rules and advice on the lockdown at the time was associated with reduced willingness to download the app.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are somewhat more at variance with another recent report on app acceptance in the U.K. [ 25 ]. That study recruited a very large sample (N ≃ 12,500) in mid-May 2020 through the Care Information Exchange (CIE), a patient-facing NHS web platform.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations